O homem e o seu entorno: metafísica e antropologia, em José Ortega y Gasset - Heleno, Gilberto (2018)
This hermeneutic and critical analysis of José Ortega y Gasset’s philosophy undertakes to examine the various circumstances from which his philosophy sprang, and to understand the metaphysical discovery of life as a radical reality and the typology of becoming human as coming from the relationship with one’s environment. Ortega creates a philosophy grounded in his people and his country. Underlying his philosophy is, on one hand, the deep crisis immersing Spain and, on the other hand, the ineffective way of facing this crisis by the Spanish people. His philosophy is an answer to an inner call and in it he takes position as a political leader and gives an intellectual reference of his time. His philosophy arises using particular circumstances: he uses newspapers, conferences, courses and classes. In this way, it reaches the Spanish people, whom Ortega wishes to educate, more quickly. The originality of his philosophy comes from his raciovitalismo, a synthesis of life and reason, giving greater emphasis on the former, since he wishes to restore life to a place it lost through rationalism, and to circumscribe reason within the broader reality of human life. According to Ortega, this is the theme of his time. His anthropology is bound to his metaphysics, since, for him, humans must undertake what is the radical reality of life as a project, as a quehacer. Depending on which answer a human gives to that call of life, which Ortega understands as a vocation, he or she becomes either a human of the masses or a noble human. By leaving behind pure reason, Ortega chose what at first he called vital reason and, later, historical reason, to understand human life, which, according to him, is built upon the dialectic of its own experiences